Expression Profile of EMT-related Genes and miRNAs Involved in Signal Transduction via the Wnt Pathway and Cadherins in Endometrial Cancer - Zmarzły, Nikola; Hermyt, Ewelina; Kruszniewska-Rajs, Celina; Gola, Joanna; Witek, Andrzej; Mazurek, Urszula; Ostenda, Aleksander; Boroń, Dariusz (Current pharmaceutical biotechnology, 2021)
Epithelial-mesenchymal transition (EMT) is a molecular reprogramming that leads to an increased ability to migrate, which can promote invasion and metastasis. EMT can be initiated in response to the activity of signaling pathways such as Wnt as well as miRNAs. The aim of the study was to determine the expression profile of EMT-related genes involved in signal transduction via the Wnt pathway and cadherins, and to assess which miRNAs can participate in the regulation of their expression. The study material consisted of 50 endometrial samples: 40 with diagnosed endometrial cancer and 10 without neoplastic changes. Expression profile of EMT-related genes was assessed with microarrays and validated by RT-qPCR. MicroRNA expression profiling was performed using microarrays. It was also determined which miRNAs may participate in the expression regulation of EMT-related genes. CDH1 overexpression was observed in all three endometrial cancer grades using both mRNA microarrays and RTqPCR. Microarray experiment showed a decrease in CDH2 level regardless of the endometrial cancer grade, however it was only partially validated with RT-qPCR. Low levels of WNT2, WNT4, WNT5A have also been observed. Decreased expression of WNT2 and WNT5A may be caused by miR-331-3p and miR-200b-5p, respectively. The Wnt signaling is disrupted in endometrial cancer, which may be due to miR-331-3p and miR-200b-5p activity. In addition, a change in WNT5A level in endometrial cancer compared to control may indicate that it acts as a suppressor gene and that its low expression is associated with tumor progression.